The nonconventional MHC class II molecule DM governs diabetes susceptibility in NOD mice. - Marc A J Morgan; Pari S S Muller; Arne Mould; Stephen A Newland; Jennifer Nichols; Elizabeth J Robertson; Anne Cooke; Elizabeth K Bikoff (PLoS ONE)
The spontaneous destruction of insulin producing pancreatic beta cells in non-obese diabetic (NOD) mice provides a valuable model of type 1 diabetes. As in humans, disease susceptibility is controlled by the classical MHC class II genes that guide CD4(+) T cell responses to self and foreign antigens. It has long been suspected that the dedicated class II chaperone designated HLA-DM in humans or H-2M in mice also makes an important contribution, but due to tight linkage within the MHC, a possible role played by DM peptide editing has not been previously tested by conventional genetic approaches. Here we exploited newly established germ-line competent NOD ES cells to engineer a loss of function allele. DM deficient NOD mice display defective class II peptide occupancy and surface expression, and are completely protected against type 1 diabetes. Interestingly the mutation results in increased proportional representation of CD4(+)Foxp3(+) regulatory T cells and the absence of pathogenic CD4(+) T effectors. Overall, this striking phenotype establishes that DM-mediated peptide selection plays an essential role in the development of autoimmune diabetes in NOD mice.